Assembly of Influenza Hemagglutinin Fusion Peptides in a Phospholipid Bilayer by Coarse-grained Computer Simulations - Collu, Francesca; Spiga, Enrico; Lorenz, Christian D.; Fraternali, Franca (Frontiers in Molecular Biosciences, 2015)
Membrane fusion is critical to eukaryotic cellular function and crucial to the entry of enveloped viruses such as influenza and human immunodeficiency virus. Influenza viral entry in the host cell is mediated by a 20-23 amino acid long sequence, called the fusion peptide (FP). Recently, possible structures for the fusion peptide (ranging from an inverted V shaped alpha-helical structure to an alpha-helical hairpin, or to a complete alpha-helix) and their implication in the membrane fusion initiation have been proposed. Despite the large number of studies devoted to the structure of the FP, the mechanism of action of this peptide remains unclear with several mechanisms having been suggested, including the induction of local disorder, promoting membrane curvature, and/or altering local membrane composition. In recent years, several research groups have employed atomistic and/or coarse-grained molecular dynamics (MD) simulations to investigate the matter. In all previous works, the behaviour of a single FP monomer was studied, while in this manuscript, we use a simplified model of a tripeptide (TP) monomer of FP (TFP) instead of a single FP monomer because each Influenza Hemagglutinin contains three FP molecules in the biological system. In this manuscript we report findings targeted at understanding the fusogenic properties and the collective behaviour of these trimers of FP peptides on a 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine model membrane. Here we show how the TFP monomers self-assemble into differently sized oligomers in the presence of the membrane. We measure the perturbation to the structure of the phospholipid membrane caused by the presence of these TFP oligomers. Our work (i) shows how self-assembly of TFP in the presence of the membrane induces non negligible deformation to the membrane and (ii) could be a useful starting point to stimulate discussion and further work targeted to fusion pore formation.